Spontaneous ripple formation in MoS2 monolayers: Electronic structure and transport effects - Miro, Pere; Ghorbani-Asl, Mahdi; Heine, Thomas (Advanced Materials, 2013)
The spontaneous formation of ripples in molybdenum disulfide (MoS 2) monolayers is investigated via density functional theory based tight-binding Born-Oppenheimer molecular dynamics. Monolayers with different lengths show spontaneous rippling during the simulations. The density of states reveals a decrease in the bandgap induced by the stretching of the MoS 2 units due to ripple formation. Significant quenching in electron conductance was also observed. The ripples in the MoS2 monolayers have an effect on the properties of the material and could impact its application in nanoelectronics. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
CRIS-Team Scopus Importer:2023-03-20
Keywords: 2D material; density functional theory; molybdenum disulfide; ripples; tight-binding